Zootechnical Additives Associated with Antimicrobials: Effects on Immune Response and Intestinal Histomorphometry in Broiler Chickens - Kenes Leonel de Morais Castro; Nilton Rohloff Júnior; Elaine Talita Santos; Jean Kaique Valentim; Rodrigo Garófallo Garcia; Giancarlo Rieger; Sarah Sgavioli (Veterinary Sciences)
This study evaluated the effects of zootechnical additives in combination with antibiotic growth promoters (AGPs) on broiler performance, leukocyte differential activity, phagocytic activity, intestinal histomorphometry, and the inside index. A total of 1400 one-day-old Cobb 500 male chicks were assigned to a completely randomized design with seven treatments and eight replicates of 25 birds per unit. The treatments included a basal diet without AGPs, a basal diet with AGPs, and AGPs combined with different zootechnical additives: prebiotics (fructooligosaccharides, galactooligosaccharides, beta-glucans, and mannan-oligosaccharides), probiotics (Bacillus subtilis LFU160), essential oils (cashew nut shell liquid), and organic acids (butyric acid glycerides). The results showed the treatments combining AGPs and zootechnical additives had better effects (p < 0.05) on weight gain, feed intake, the feed conversion ratio, and the productive efficiency index. The phagocytic activity was worse in birds without AGPs and with AGPs but without additives. However, birds that received AGPs in combination with zootechnical additives exhibited a poorer intestinal histomorphometry and lower inside index compared to those fed only AGPs or diets without AGPs. In conclusion, zootechnical additives can be used alongside AGPs to enhance broiler performance and immune function, particularly during early growth stages, with essential oils showing the most promising results.